2018
DOI: 10.1007/s10926-018-9801-y
|View full text |Cite
|
Sign up to set email alerts
|

Return-to-Work Following Depression: What Work Accommodations Do Employers and Human Resources Directors Put in Place?

Abstract: The magnitude of economic and social costs related to common mental disorders has a profound impact on the workplace. Returning to work following depression is, therefore, a major issue for all stakeholders involved (employee, employer, human resources director, union, physician, etc.). Considering their role in the organization, Human Resources Directors (HRD) and employers have a decisive impact on the return-to-work (RTW) process. Purpose This study aims to determine which RTW accommodations are implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 52 publications
1
26
0
1
Order By: Relevance
“…As seen in the second building block in the key process of enhancing managerial agency, making work adjustments are important in an RTW processes for which the employer is responsible [23]. In contrast to the present intervention, it has been found that adjustments are rarely based on employee needs or functional limitations [51]. Employers have reported uncertainty regarding work accommodations for employees with mental health problems [25].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…As seen in the second building block in the key process of enhancing managerial agency, making work adjustments are important in an RTW processes for which the employer is responsible [23]. In contrast to the present intervention, it has been found that adjustments are rarely based on employee needs or functional limitations [51]. Employers have reported uncertainty regarding work accommodations for employees with mental health problems [25].…”
Section: Discussionmentioning
confidence: 92%
“…That study highlighted how perfectionism, high sense of responsibility, and difficulty in setting limits in demanding work situations can be obstacles in RTW [ 28 ]. Since the employee may have trouble seeing their own needs, it is especially important that the manager knows how to detect early signs of stress [ 26 ] and to provide timely support. Our results indicate that managers learned how to do this.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations